Motivation of Domestic Tourists Visiting Bongkasa Pertiwi Village, Bali, Indonesia - Andreyana, I Gede Eka (LACULTOUR: Journal of Language and Cultural Tourism, 2024)
This research, employing a quantitative descriptive approach, aims to understand the motivation of domestic tourists visiting Bongkasa Pertiwi Village, viewed from the dimensions of push and pull factors. Data were collected through questionnaires distributed to 100 respondents and analyzed using confirmatory factor analysis. The results of the study indicate that among the nine push factor dimensions and six pull factors investigated, each has dominant factors influencing domestic tourists to visit Bongkasa Pertiwi Village. The dominant push factors are: 1) wanting to enjoy a different atmosphere and environment, 2) wanting to enjoy the journey, 3) wanting to enjoy tourist attractions for pleasure, 4) wanting to spend time with friends or family, 5) wanting to impress family and friends, 6) wanting to meet and interact with new people, 7) wanting to learn about new cultures, 8) wanting to improve skills and self-evaluate, and 9) wanting to visit a place they have long wanted to visit. Meanwhile, the six dominant pull factors for tourists are: 1) affordable rental facility prices, 2) interesting historical sites, 3) good weather and climate, 4) strategic location, 5) comprehensive tourism facilities, and 6) safety from criminal acts.